2021
DOI: 10.3390/ijerph182212236
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence the Judgment of Oral Management Necessity in Preoperative Oral Screening

Abstract: Oral management during the perioperative period is important to prevent the development of postoperative complications. However, there are no unified systems to examine the oral status of patients and very few studies have focused on preoperative oral screening. In this study, we examined the oral status of patients who underwent oral screening at a University Hospital. A total of 1173 patients who underwent oral screening for perioperative management from April 2020 to July 2021 were enrolled. The subjects’ m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…ASA practice advisories suggest POC benefits from a variety of interventions 17) . However, only a few studies report beneficial effects of the POC on clinical outcomes, mostly by exploring impacts of interventions provided by a single profession alone [5][6][7][8][9][10][11] .…”
Section: Roles Of the Pocmentioning
confidence: 99%
See 1 more Smart Citation
“…ASA practice advisories suggest POC benefits from a variety of interventions 17) . However, only a few studies report beneficial effects of the POC on clinical outcomes, mostly by exploring impacts of interventions provided by a single profession alone [5][6][7][8][9][10][11] .…”
Section: Roles Of the Pocmentioning
confidence: 99%
“…Organizational designs of the POC can roughly be divided into single-professional and multiprofessional models 4) . Various studies regarding single-professional models have been reported [5][6][7][8][9][10][11] . However, studies of multi-professional models remain limited, and the benefits of preoperative evaluation provided by multi-professional POC teams remain to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Multidisciplinary health care in various fields, such as stroke rehabilitation, 1 perioperative oral management 2 and palliative care, 3,4 aims to improve the quality of health care and life through early detection of disease, promotion of recovery and prevention of serious illness. In addition, multidisciplinary health care reduces the burden on medical personnel by improving medical efficiency and safety through the standardisation and organisation of medical care.…”
Section: Introductionmentioning
confidence: 99%